EVALUASI PENGGUNAAN LAHAN PERMUKIMAN BERBASIS ANALISIS RISIKO BENCANA TSUNAMI KOTA PADANG - Alfonsus Jimmy Hutabarat; Ahyuni Ahyuni (JURUSAN GEOGRAFI FIS UNP, 2021)
This study purposed for know about : (1) the level of vulnerability, threats (hazard) and risk of Tsunami disaster in Padang City, and (2) to evaluate areas of settlement that are at risk of a tsunami disaster in Padang city. The research method uses a quantitive descriptive method. The type of data is primary and secondary data from The Central Statistic Agency of Padang City and Geospatial Information Agency. Based on this research the conclusion is : (1) the highest level of tsunami risk is in the three district that is Padang Selatan, Padang Barat and Padang Timur based on the variables of: population density, settlement densities, evacuation rate, distance from the coastline and surface level (2) the area of existing settlement landuse in Padang City in 2018 is 8021.829 hectare or 11.54% of the total area of Padang City administration area, while the use of affected settlement land is 4744.578 Hectare or 59.14% from the total settlement landuse area.